Within / Beyond Borders : The Collection of the European Investment Bank at Banco de Portugal - da Silva Costa, Carlos; Hoyer, Werner; Munro, Delphine (S.l. : Banco de Portugal : EIB European Investment Bank, 2014)
Ivanov, Pravdoliub ; Boltanski, Christian ; Guerresi, Maïmouna P. ; Bismuth, Pierre ; Cragg, Tony ; Kulik, Zofia ; Kolehmainen, Ola ; Graubner, Gotthard ; Jodice, Mimmo ; Esser, Elger ; Puranen, Jorma ; IRWIN ; Innes, Callum ; Cabrita Reis, Pedro ; Morellet, François ; Scully, Sean ; Callery, Simon ; Plensa, Jaume ; Parmiggiani, Claudio ; Kounellis, Jannis ; Kapoor, Anish ; Fabre, Jan ; Rae, Fiona ; Calapez, Pedro ; Dumas, Marlene ; Sarmento, Julião
Within / Beyond Borders. The Collection of the European Investment Bank at Banco de Portugal, 15 May - 5 September 2014
boek